2018
DOI: 10.1016/j.jnc.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding and post-sampling strategies to discover non-indigenous species: A case study in the estuaries of the central south Bay of Biscay

Abstract: Metabarcoding and post-sampling strategies to discover non-indigenous species: a case study in the estuaries of the central south Bay of Biscay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
(64 reference statements)
3
20
0
Order By: Relevance
“…A similar result was also reported by Borrell, et al . 64 who investigated the applicability of these two markers to detect NIS in estuaries. The most likely explanation for this result is that the rate of evolution in the COI gene is much faster than in the 18S rRNA and therefore there is greater sequence variability between species 65 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was also reported by Borrell, et al . 64 who investigated the applicability of these two markers to detect NIS in estuaries. The most likely explanation for this result is that the rate of evolution in the COI gene is much faster than in the 18S rRNA and therefore there is greater sequence variability between species 65 .…”
Section: Discussionmentioning
confidence: 99%
“…This means that false negatives (i.e., failure to detect a species when it is present) are a much greater concern for traditional methods, and significant investment of time and effort will be required to confidently detect species at low densities. eDNA surveys can complement traditional surveys by guiding subsequent unambiguous surveys in a targeted, site‐specific, species‐specific and cost‐efficient manner (e.g., Borrell et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Leduc et al 2019, Huhn et al 2020, Rey et al 2020, Westfall et al 2020). Currently, it would probably work best as an early alert system or exploratory method to be used as a complement to conventional approaches such as in situ visual confirmation (Borrell et al 2018, Holman et al 2019, Rey et al 2020, specimen collection (Leduc et al 2019, Huhn et al 2020 or followed by active surveillance with digital drop PCR (ddPCR) or quantitative PCR (qPCR) (Wood et al 2019).…”
Section: Sampled Locations Substrates and Biological Targetsmentioning
confidence: 99%
“…We found that most of the studies have sampled multiple ports or marinas (e.g. Brown et al 2016, Leduct et al 2019, or estuaries (Borrell et al 2018), and multiple sites within each port/marina/estuary (Abad et al 2016, Leduc et al 2019, Rey et al 2020. In order to detect the majority of taxa in a given location, in particular rare and/or patchy species, biodiversity surveys require comprehensive spatial and temporal sampling and screening of different types of substrates (e.g.…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation